Long-Term Oocyte-Like Cell Development in Cultures Derived from Neonatal Marmoset Monkey Ovary. (9th November 2015) - Fereydouni, Bentolhoda; Salinas-Riester, Gabriela; Heistermann, Michael; Dressel, Ralf; Lewerich, Lucia; Drummer, Charis; Behr, Rüdiger
Abstract : We use the common marmoset monkey ( Callithrix jacchus ) as a preclinical nonhuman primate model to study reproductive and stem cell biology. The neonatal marmoset monkey ovary contains numerous primitive premeiotic germ cells (oogonia) expressing pluripotent stem cell markers including OCT4A (POU5F1). This is a peculiarity compared to neonatal human and rodent ovaries. Here, we aimed at culturing marmoset oogonia from neonatal ovaries. We established a culture system being stable for more than 20 passages and 5 months. Importantly, comparative transcriptome analysis of the cultured cells with neonatal ovary, embryonic stem cells, and fibroblasts revealed a lack of germ cell and pluripotency genes indicating the complete loss of oogonia upon initiation of the culture. From passage 4 onwards, however, the cultured cells produced large spherical, free-floating cells resembling oocyte-like cells (OLCs). OLCs strongly expressed several germ cell genes and may derive from the ovarian surface epithelium. In summary, our novel primate ovarian cell culture initially lacked detectable germ cells but then produced OLCs over a long period of time. This culture system may allow a deeper analysis of early phases of female primate germ cell development and—after significant refinement—possibly also the production of monkey oocytes.